Liquid crystal polymer film
By forming an appropriate amount of pores on the surface of the liquid crystal polymer film and forming a conductive metal film without roughening the film surface, the problem of insufficient adhesion between the liquid crystal polymer film and the resin layer and the metal layer is solved, and excellent adhesion and bonding strength are achieved.
Patent Information
- Application Number
- CN202411358522.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-05
- Filing Date
- 2024-09-27
- Publication Date
- 2025-04-08
AI Technical Summary
The adhesion between the conventional liquid crystal polymer film and the resin layer and the metal layer is insufficient, resulting in challenges in improving the adhesion between the liquid crystal polyester film and the conductive metal film.
By forming a hole on the surface of the liquid crystal polymer film, the area ratio of the hole is ensured to be 0.50% or more, and without roughening the film surface, a conductive metal film is formed by a plating method to achieve excellent adhesion.
A liquid crystal polymer film and its laminate are realized that it can have excellent adhesion even if the film surface is not roughened, thereby improving the bonding strength between the liquid crystal polymer film and the conductive metal film.
Smart Images

Figure CN119775626A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a liquid crystal polymer film and a laminate. Background Art
[0002] Liquid crystal polymer has low moisture absorption rate and low dielectric constant. Therefore, liquid crystal polymer film using liquid crystal polymer is increasingly used as an insulating layer of FPC (Flexible printed circuits), for example.
[0003] The liquid crystal polymer film as the insulating layer is used by being laminated on a metal layer such as copper foil together with other resin layers or alone. However, the adhesion between the liquid crystal polymer film and the resin layer or metal layer is insufficient.
[0004] Therefore, in order to improve the adhesion between the liquid crystal polyester film and the conductive metal film, the following method for manufacturing a metal-coated liquid crystal polyester substrate has been proposed: a conductive metal film is formed on the surface of a liquid crystal polyester film to obtain the metal-coated liquid crystal polyester substrate, the film surface is roughened using an etching solution, and then a conductive metal film is formed on the roughened film surface by a plating method, and then the liquid crystal polyester film formed with the conductive metal film is heated to a given temperature selected from a range from 100°C to near the liquid crystal transition temperature (see Patent Document 1). Prior art literature Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2004-307980 Summary of the invention Problems to be solved by the invention
[0006] The method of Patent Document 1 requires a step of roughening the film surface using an etching solution.
[0007] An object of the present invention is to provide a liquid crystal polymer film having excellent adhesion even without roughening the film surface, and a laminate having the liquid crystal polymer film. Technical solutions to solve problems
[0008] That is, the present invention includes the following contents.
[0009] [1] A liquid crystal polymer film, wherein The liquid crystal polymer film has pores on the surface, When the surface of the liquid crystal polymer film is observed, the area ratio of the pores to the surface is 0.50% or more. [2] The liquid crystal polymer film according to [1], wherein the liquid crystal polymer film is a porous film. [3] The liquid crystal polymer film according to [1] or [2], wherein the average size of the pores is 10 μm or less. [4] A laminate comprising: the liquid crystal polymer film according to any one of [1] to [3]; a thermoplastic resin layer; and a conductor layer. Effects of the Invention
[0010] According to the present invention, there can be provided a liquid crystal polymer film having excellent adhesion even without roughening the film surface, and a laminate having the liquid crystal polymer film. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 This is a schematic cross-sectional view of an example of the laminate of the present invention. DETAILED DESCRIPTION
[0012] (Liquid Crystal Polymer Film) The liquid crystal polymer film of the present invention has pores on the surface. When the surface of the liquid crystal polymer film is observed, the area ratio of the pores to the surface is 0.50% or more.
[0013] When the surface of the liquid crystal polymer film is observed, by setting the area ratio of the pores to the surface to 0.50% or more, a liquid crystal polymer film having excellent adhesion to other layers can be obtained. The upper limit of the area ratio is not particularly limited, but from the viewpoint of more excellent adhesion, the area ratio is preferably 10.00% or less, more preferably 7.00% or less, and particularly preferably 5.00% or less.
[0014] The average size of the pores in the liquid crystal polymer film is not particularly limited, but is preferably 100 μm or less, more preferably 50 μm or less, further preferably 10 μm or less, and particularly preferably 5.0 μm or less from the viewpoint of better adhesion. The lower limit of the average pore size is not particularly limited, but the average pore size is preferably 0.1 μm or more, more preferably 0.5 μm or more, and particularly preferably 1.0 μm or more.
[0015] The area ratio and the average pore size were calculated as follows. Platinum is deposited on the surface of the liquid crystal polymer film to obtain an observation sample. The surface of the observation sample is observed by SEM (scanning electron microscope; for example, SU8020, manufactured by Hitachi High-Technologies Corporation, accelerating voltage 2.0 kV) to obtain a SEM image. The obtained SEM image is subjected to image analysis. Image analysis is performed, for example, using Image-J, which is a public image processing software. Specifically, it is performed as follows. Import the SEM image into Image-J. Calculate the area ratio of the holes based on the number of pixels of the holes that are relatively dark in the SEM image and the number of pixels of other parts. For the hole size, the longest part of the hole is set as the hole size. The average hole size is calculated by dividing the sum of the hole sizes by the number of holes. When the SEM image was loaded into Image-J, black-and-white binarization was performed to distinguish the pores from other parts. The standard conditions of Image-J were used for the threshold value during the binarization process.
[0016] The liquid crystal polymer film contains a liquid crystal polymer. The liquid crystal polymer is not limited. The liquid crystal polymer is a liquid crystal thermoplastic resin. As the liquid crystal polymer, for example, a liquid crystal polyester can be mentioned, and preferably an aromatic liquid crystal polyester can be mentioned. The liquid crystal polymer is specifically described in, for example, Japanese Patent Publication No. 2020-147670 and Japanese Patent Publication No. 2004-189867. The liquid crystal polymer may be a commercial product, for example, UENO LCP (registered trademark, the same below) 8100 series (low melting point type, manufactured by Ueno Pharmaceutical Co., Ltd.) and UENO LCP 5000 series (high melting point type, manufactured by Ueno Pharmaceutical Co., Ltd.). Preferably, UENO LCP 5000 series is used.
[0017] The melting point of the liquid crystal polymer is not limited. The melting point of the liquid crystal polymer is, for example, above 200°C, preferably above 220°C, more preferably above 250°C, and, for example, below 370°C. The melting point of the liquid crystal polymer is determined by differential scanning calorimetry. In the differential scanning calorimetry, the heating rate is 10°C / min, for example, the range of operation from 25°C to 400°C, and the liquid crystal polymer is heated under a nitrogen atmosphere. In addition, if the liquid crystal polymer is a commercial product, the catalog value of the commercial product can be directly used. If the melting point of the liquid crystal polymer is below the above upper limit, the porous liquid crystal polymer film has excellent handleability and processability. If the melting point of the liquid crystal polymer is above the above lower limit, the porous liquid crystal polymer film has excellent heat resistance.
[0018] The glass transition temperature of the liquid crystal polymer is not limited. The glass transition temperature of the liquid crystal polymer is, for example, 80° C. or higher and, for example, 125° C. or lower. The glass transition temperature of the liquid crystal polymer is determined by differential scanning calorimetry at a heating rate of 10° C. / min.
[0019] The content of the liquid crystal polymer in the liquid crystal polymer film is not particularly limited, but is preferably 70% by mass or more based on the liquid crystal polymer film.
[0020] The liquid crystal polymer film may also contain other components. Examples of other components include fillers, additives, and resins other than liquid crystal polymers.
[0021] Examples of the filler include inorganic fillers such as silica, alumina, titanium oxide, barium titanate, strontium titanate, aluminum hydroxide, and calcium carbonate; and organic fillers such as cured epoxy resins, cross-linked benzoguanamine resins, and cross-linked acrylic resins. When the filler is contained, the content of the filler in the liquid crystal polymer film is not particularly limited, but is preferably 20% by volume to 70% by volume.
[0022] Examples of the additive include a leveling agent, a defoaming agent, an antioxidant, an ultraviolet absorber, a flame retardant, and a colorant. The content of the additive in the liquid crystal polymer film is not particularly limited, but is preferably 0 to 5 parts by mass based on 100 parts by mass of the liquid crystal polymer.
[0023] Examples of resins other than liquid crystal polymers include thermoplastic resins such as polypropylene, polyamide, amorphous polyester, polyphenylene sulfide, polyether ketone, polycarbonate, polyether sulfone, polyphenylene ether, and polyether imide; and thermosetting resins such as phenolic resins, epoxy resins, polyimide resins, and cyanate resins. The content of the resin other than the liquid crystal polymer is not particularly limited, but is preferably 0 to 20 parts by mass based on 100 parts by mass of the liquid crystal polymer.
[0024] The thickness of the liquid crystal polymer film is not particularly limited, but is, for example, 2 μm or more, preferably 5 μm or more, more preferably 10 μm or more, and, for example, 200 μm or less, preferably 100 μm or less, more preferably 75 μm or less.
[0025] The liquid crystal polymer film may be a porous film or may not be a porous film. When the liquid crystal polymer film is a porous film, the porosity of the liquid crystal polymer film is not particularly limited, but is preferably 20% to 70%. The method for determining the porosity of the liquid crystal polymer film is described in the following Examples.
[0026] The relative dielectric constant of the liquid crystal polymer film under 10 GHz conditions is, for example, less than 3.10, preferably less than 2.90, more preferably less than 2.80, and further preferably less than 2.75. If the relative dielectric constant of the liquid crystal polymer film is less than the above upper limit, the liquid crystal polymer film is a low dielectric. The lower limit of the relative dielectric constant of the liquid crystal polymer film under 10 GHz conditions is not limited. For example, the lower limit of the relative dielectric constant of the liquid crystal polymer film under 10 GHz conditions is 1.00. The method for determining the relative dielectric constant of the liquid crystal polymer film is described in the following embodiments.
[0027] The dielectric loss tangent of the liquid crystal polymer film at 10 GHz is, for example, 0.0030 or less, preferably 0.0025 or less, more preferably 0.0020 or less, further preferably 0.0010 or less, and particularly preferably 0.00070 or less. If the dielectric loss tangent of the liquid crystal polymer film is below the above upper limit, the liquid crystal polymer film is low dielectric. The lower limit of the dielectric loss tangent of the liquid crystal polymer film under the condition of 10 GHz is not limited. For example, the lower limit of the dielectric loss tangent of the liquid crystal polymer film under the condition of 10 GHz is 0.00000. The method for measuring the dielectric loss tangent of the liquid crystal polymer film is described in the following examples.
[0028] <Applications of Liquid Crystal Polymer Film> The use of the liquid crystal polymer film is not limited. Examples of the use of the liquid crystal polymer film include an insulating layer of a wired circuit board and an antenna board for wireless communication.
[0029] <Method for producing liquid crystal polymer film> The method for producing the liquid crystal polymer film is not particularly limited as long as the liquid crystal polymer film of the present invention can be obtained. As an example of a method for producing a liquid crystal polymer film, a method for producing a porous liquid crystal polymer film is mentioned. The method for producing a porous liquid crystal polymer film includes, for example, a film forming step and a porous forming step. The porous process may be performed by extraction or foaming. In addition, the extraction method may be solvent extraction or supercritical extraction. Hereinafter, as the porous forming step, an extraction step using a supercritical fluid is mentioned.
[0030] <<Film production process>> The film forming step is a step of forming a film of a composition containing a liquid crystal polymer and a pore-forming agent.
[0031] <<<Liquid Crystal Polymer>>> Examples of the liquid crystal polymer include the above-mentioned liquid crystal polymers.
[0032] <<<Porosifying agent>>> The porogen is a component dispersed in the liquid crystal polymer in order to make the liquid crystal polymer porous. As the pore-forming agent, for example, a compound that undergoes phase separation with the liquid crystal polymer at a kneading temperature (described later) can be cited. Phase separation includes the situation where a certain shape is ensured in the kneaded material without being dissolved in the liquid crystal polymer. In addition, as the pore-forming agent, preferably a compound that does not thermally decompose at the kneading temperature can be cited. The pore-forming agent is not particularly limited, and examples thereof include organic compounds and inorganic compounds.
[0033] <<<<Organic compounds>>>> Examples of the organic compound include: polyalkylene glycols such as polyethylene glycol and polypropylene glycol; products of the polyalkylene glycols that are methyl-capped at one or both ends, or products of the polyalkylene glycols that are (meth)acrylate-capped at one or both ends; compounds of polyalkylene glycols such as phenoxypolyethylene glycol (meth)acrylate in which one end is capped with an alkyl group or an aryl group and the other end is capped with a (meth)acrylate; urethane prepolymers; polyol poly(meth)acrylates such as trimethylolpropane tri(meth)acrylate and dipentaerythritol hexa(meth)acrylate; (meth)acrylate compounds such as ε-caprolactone (meth)acrylate, urethane (meth)acrylate, epoxy (meth)acrylate, and oligoester (meth)acrylate; and the like. In addition, examples of organic compounds include purine derivatives, and examples of purine derivatives include caffeine.
[0034] <<<<Inorganic compounds>>>> Since the inorganic compound is insoluble in the liquid crystal polymer, it undergoes phase separation from the liquid crystal polymer at a kneading temperature (described later).
[0035] The inorganic compound is not particularly limited, and examples thereof include inorganic salts, inorganic oxides, inorganic nitrides, inorganic sulfides, etc. Among them, inorganic salts are preferred because they are easily extracted in the extraction step.
[0036] The inorganic salt may be an anhydrous form or a hydrate, but is preferably an anhydrous form. The inorganic salt is not particularly limited, but examples thereof include metal halides, metal nitrates, metal sulfates, metal carbonates, etc. Among them, metal halides are preferred from the perspective of being easily extracted in the extraction step. Examples of the halogen in the metal halide include fluorine, chlorine, bromine, and iodine. Among them, chlorine and bromine are preferred. The metal in the inorganic salt is not particularly limited, but is preferably an alkali metal or an alkaline earth metal. Examples of the alkali metal include lithium, sodium, potassium, rubidium, cesium, and francium. Among them, lithium, sodium, and potassium are preferred. Examples of the alkaline earth metal include beryllium, magnesium, calcium, strontium, barium, and radium, among which calcium is preferred.
[0037] The metal halide is preferably at least one of an alkali metal halide and an alkaline earth metal halide. Examples of the alkali metal halide include lithium chloride, sodium chloride, potassium chloride, lithium bromide, sodium bromide, and potassium bromide. Examples of the alkaline earth metal halide include calcium chloride and calcium bromide.
[0038] The melting point of the pore-forming agent is preferably higher than the melting point (Tm) of the liquid crystal polymer, more preferably at least 10° C. higher than the melting point of the liquid crystal polymer, and particularly preferably at least 20° C. higher than the melting point of the liquid crystal polymer. The melting point of the inorganic compound is preferably, for example, the melting point of the liquid crystal polymer + 600° C. or less. The melting point of the inorganic compound can be determined, for example, by the same method as the method for measuring the melting point of the liquid crystal polymer. The temperature range of differential scanning calorimetry in measuring the melting point of the inorganic compound is, for example, 25°C to 1000°C.
[0039] The pore-forming agent is usually provided in a powder state for kneading. The average particle size of the pore-forming agent is not particularly limited and can be appropriately determined depending on the degree of pore formation, the thickness of the porous liquid crystal polymer film, and the like. The average particle size of the powdered pore-making agent is, for example, 0.001 mm to 0.8 mm, preferably 0.003 mm to 0.6 mm, and more preferably 0.005 mm to 0.4 mm. The average particle size can be measured using a laser diffraction / scattering particle size distribution measuring apparatus.
[0040] The mixing ratio of the liquid crystal polymer and the porogen is not limited. The mixing ratio of the liquid crystal polymer and the porogen is appropriately adjusted so that the obtained porous liquid crystal polymer film becomes the desired porosity. Specifically, the percentage of the volume of the porogen relative to the total volume of the liquid crystal polymer and the porogen is, for example, 20% by volume or more, preferably 30% by volume or more, more preferably 40% by volume or more, and, for example, 90% by volume or less, preferably 80% by volume or less, more preferably 70% by volume or less. It should be noted that the percentage of the volume of the porogen relative to the total volume of the liquid crystal polymer and the porogen is calculated by converting the mass of the porogen relative to the total mass of the liquid crystal polymer and the porogen using a specific gravity.
[0041] The composition may further contain an additive. The additive is different from the pore-forming agent. As an additive, for example, a filler can be cited. As a filler, for example, a hollow sphere can be cited. Hollow spheres include, for example, glass spheres. Hollow spheres are described in, for example, Japanese Patent Publication No. 2004-189867.
[0042] When the composition contains hollow spheres, a porous liquid crystal polymer film having a high porosity can be produced.
[0043] On the other hand, if the composition does not contain hollow spheres, it is possible to suppress the porous liquid crystal polymer film from becoming brittle.
[0044] The composition is obtained by kneading a liquid crystal polymer and a pore-forming agent, for example.
[0045] The kneading temperature during kneading is not limited. The kneading temperature during kneading is, for example, in the range of ±30°C of the melting point of the liquid crystal polymer (i.e., in the case where the melting point of the liquid crystal polymer is 280°C, it is 250°C or more and 310°C or less), preferably in the range of ±20°C of the melting point of the liquid crystal polymer, more preferably in the range of ±10°C of the melting point of the liquid crystal polymer, and further preferably in the range of ±5°C of the melting point of the liquid crystal polymer. In addition, the kneading temperature during kneading is, for example, the melting point of the pore-forming agent - 5°C or less, preferably the melting point of the pore-forming agent - 10°C or less, and more preferably the melting point of the pore-forming agent - 20°C or less. In other words, the melting point of the pore-forming agent is, for example, 5°C or more higher than the kneading temperature, preferably 10°C or more higher than the kneading temperature, and more preferably 20°C or more higher than the kneading temperature.
[0046] In the film forming step, the composition containing the liquid crystal polymer and the pore-forming agent is formed into a film. Examples of methods for forming the composition into a film include pressing, extrusion, and injection. Preferably, pressing is used, and more preferably, hot pressing is used. The temperature of the hot press is not limited. Specifically, the temperature of the hot press is, for example, 200° C. to 400° C. In addition, the temperature of the hot press is, for example, preferably 5° C. or more higher than the melting point of the liquid crystal polymer. The pressing pressure is, for example, 1 MPa or more, preferably 4 MPa or more, and for example, 20 MPa or less, preferably 10 MPa or less. Thus, a nonporous film (nonporous sheet) containing a liquid crystal polymer and a pore-forming agent is obtained.
[0047] The thickness of the nonporous film is not particularly limited. For example, the thickness of the nonporous film is appropriately set according to the target thickness of the porous liquid crystal polymer film.
[0048] <Extraction process> The extraction step is a step of extracting the porogen from the membrane using a supercritical fluid. Specifically, the porogen in the nonporous membrane is extracted using a supercritical fluid. For example, a supercritical device is used in the extraction process. The supercritical device includes a pressure vessel and a circulation device. The pressure vessel can contain a supercritical fluid while circulating it inside. The circulation device circulates the supercritical fluid in the pressure vessel. In addition, a recovery device is provided in the circulation device. The recovery device removes the pore-forming agent extracted by the supercritical fluid 15.
[0049] <<Supercritical fluid>> The type of supercritical fluid is not limited. Examples of the supercritical fluid include supercritical carbon dioxide and supercritical nitrogen. From the viewpoint of production cost, the supercritical fluid is preferably supercritical carbon dioxide.
[0050] <<Entrainer (Japanese: エンレーナ)>> An entrainer may be added to the supercritical fluid. In other words, the extraction process may be performed in the presence of an entrainer. In order to improve the extraction efficiency of the pore-forming agent by the supercritical fluid, the entrainer is added to the supercritical fluid. Examples of the entrainer include water, alcohol compounds, ketone compounds, ester compounds, aromatic compounds, long-chain alkyl compounds, and aprotic amide compounds. These can be used alone or in combination.
[0051] Examples of the alcohol compound include alcohols having 1 to 3 carbon atoms. Examples of the alcohols having 1 to 3 carbon atoms include methanol, ethanol, and propanol. Examples of the ketone compound include acetone and methyl ethyl ketone. Examples of the ester compound include methyl acetate, ethyl acetate, and propyl acetate. Examples of the aromatic compound include benzene, toluene, and xylene. Examples of the long-chain alkyl compound include pentane, hexane, and heptane. Examples of the aprotic amide compound include N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), and dimethylacetamide (DMAC). Preferred examples of the entrainer include alcohol compounds, ester compounds, and aprotic amide compounds.
[0052] The mixing ratio of the entrainer is appropriately set. Specifically, with respect to the circulation flow rate of the supercritical fluid of 100 mL / min, the blending flow rate of the entrainer is, for example, 0.1 mL / min or more, preferably 1 mL / min or more, and, for example, 20 mL / min or less, preferably 5 mL / min or less. The blending ratio of the entrainer to the supercritical fluid used is, for example, 5.0 wt % or more, preferably 10 wt % or more, and, for example, 50 wt % or less, preferably 40 wt % or less.
[0053] The non-porous membrane is placed in a pressure vessel. Then, a supercritical fluid is flowed into the pressure vessel in a supercritical device. Then, the supercritical fluid is circulated by a circulation device. Thus, the supercritical fluid contacts the non-porous membrane.
[0054] Thus, first, the supercritical fluid outside the non-porous membrane is impregnated into the non-porous membrane. That is, the supercritical fluid penetrates into the interior of the non-porous membrane. Thus, the supercritical fluid dissolves the porogen while returning to the outside of the non-porous membrane. Thus, the porogen is extracted from the non-porous membrane using the supercritical fluid.
[0055] The conditions of the extraction process are not limited. The temperature of the supercritical fluid is, for example, higher than the glass transition temperature of the above-mentioned liquid crystal polymer. In addition, the temperature of the supercritical fluid is, for example, at least 10°C higher than the glass transition temperature of the above-mentioned liquid crystal polymer, preferably at least 30°C higher, more preferably at least 50°C higher, and further preferably 70°C higher. As described above, if the temperature of the supercritical fluid is higher than the glass transition temperature of the liquid crystal polymer, the extraction efficiency of the supercritical fluid in the extraction process can be improved. Therefore, a porous liquid crystal polymer film with a high porosity can be manufactured. The temperature of the supercritical fluid is, for example, above 40°C, preferably above 75°C, more preferably above 110°C, further preferably above 120°C, particularly preferably above 150°C, most preferably above 170°C, and, for example, below 200°C, preferably below 190°C, and more preferably below 180°C.
[0056] The pressure of the supercritical fluid is, for example, 10 MPa or more, preferably 20 MPa or more, and, for example, 35 MPa or less, preferably 30 MPa or less.
[0057] The extraction time is, for example, more than 20 minutes, preferably more than 1 hour, more preferably more than 3 hours, further preferably more than 5 hours, particularly preferably more than 8 hours, most preferably more than 10 hours, and, for example, less than 100 hours, preferably less than 48 hours, more preferably less than 24 hours. If the extraction time is more than the above lower limit, the extraction efficiency of the supercritical fluid in the extraction process can be improved, and a porous liquid crystal polymer film with a high porosity can be manufactured. If the extraction time is less than the above upper limit, the production cycle can be shortened, and the manufacturing efficiency can be improved.
[0058] The extraction rate of the pore-forming agent from the membrane is not particularly limited, but is preferably 5% or more, more preferably 10% or more, and particularly preferably 20% or more. The extraction rate of the pore-forming agent from the membrane is not particularly limited, but is preferably 100% or less. The greater the extraction rate, the greater the porosity. In this regard, the extraction rate is preferably 5% or more.
[0059] While removing the supercritical fluid inside the pressure vessel, the pressure of the pressure vessel is reduced. Specifically, the pressure of the pressure vessel is restored to atmospheric pressure. The speed of pressure reduction is not limited. For example, the speed of pressure reduction is adjusted to suppress the foaming caused by the supercritical fluid impregnated in the non-porous membrane. At this time, the pressure vessel may be heated or not. The heating temperature is the same as the temperature of the supercritical fluid in the extraction, for example, 40°C or more, preferably 75°C or more, more preferably 110°C or more, further preferably 120°C or more, particularly preferably 150°C or more, most preferably 170°C or more, and, for example, 200°C or less, preferably 190°C or less, more preferably 180°C or less. The heating time is, for example, 10 minutes or more and 3 hours or less. That is, in one example, before the pressure of the pressure vessel is restored to atmospheric pressure, the heating temperature is pre-set to the same temperature as the supercritical fluid in the extraction, and after the pressure of the pressure vessel is restored to atmospheric pressure, the heating temperature may be maintained or the heating may be stopped.
[0060] According to the above description, a plurality of pores are formed instead of the pore-forming agent impregnated in the non-porous film, thereby manufacturing a porous liquid crystal polymer film.
[0061] The porous liquid crystal polymer film has a thickness and a film shape. The film shape includes a sheet shape. The porous liquid crystal polymer film extends in a plane direction. The plane direction is orthogonal to the thickness direction. The porous liquid crystal polymer film has a large number of fine pores (pores). In addition, as the bubble structure of the porous liquid crystal polymer film, for example, an independent bubble structure, a continuous bubble structure, and a semi-independent semi-continuous bubble structure can be cited. From the viewpoint of the processability of the circuit substrate, an independent bubble structure (single bubble structure) is preferred. This is because, for example, when making a circuit substrate, if a plating treatment is performed on the basis of drilling holes using a drill, laser, etc., the plating liquid intrudes from the porous portion exposed by the drilling holes, and the conductor layer precipitates such a problem (immersion plating liquid); or, when the porous film is attached to the copper foil, the holes are crushed by hot pressing (pressure resistance).
[0062] The fact that the porous liquid crystal polymer film has a single cell structure can be confirmed using a penetrant used in a penetrant flaw detection test specified in JIS (JIS Z 2343-1, etc.). It is preferred to use a liquid having a contact angle of 25° or less with respect to the polymer surface and a viscosity of 2.4 mm 2 / s (37.8°C) of permeation liquid. That is, the porous liquid crystal polymer film is cut approximately perpendicularly to the surface to expose the porous cross section, and the cross section is immersed in a permeation liquid such as a red permeation liquid for 5 minutes, and the immersion length (the distance the permeation liquid penetrates from the cross section) is measured. When the immersion length is 500 μm or less, and further 300 μm or less, it can be said that the structure of the porous liquid crystal polymer film is a single bubble structure.
[0063] (Laminated body) The laminated body of the present invention comprises the liquid crystal polymer film of the present invention, a thermoplastic resin layer, and a conductor layer.
[0064] <Thermoplastic resin layer> As the thermoplastic resin layer, for example, a known thermoplastic resin film used for an insulating layer can be used. Examples of the thermoplastic resin layer include a multilayer aromatic polyimide film, a single-layer polyimide film, a polyester film, a polyamide film (including an aromatic polyamide film), a vinyl ester film, and a fluororesin film. The thickness of the thermoplastic resin layer is not particularly limited, but is, for example, 5 μm to 1000 μm, preferably 7 μm to 800 μm, and more preferably 10 μm to 500 μm.
[0065] <Conductor layer> The conductor layer has a sheet (plate) shape. The material of the conductor layer is not particularly limited, and examples thereof include copper, iron, silver, gold, aluminum, nickel, and alloys thereof (stainless steel, bronze), etc. Preferably, copper is used. The thickness of the conductor layer is, for example, 0.1 μm or more, preferably 1 μm or more, and, for example, 100 μm or less, preferably 50 μm or less.
[0066] An example of the laminated body of the present invention will be described with reference to the drawings. Figure 1 1 is a schematic cross-sectional view of an example of the laminate of the present invention. The laminate includes a conductor layer 1, a thermoplastic resin layer 2, and a liquid crystal polymer film 3 in this order. [Example]
[0067] The present invention will be described in more detail below by showing examples and comparative examples. It should be noted that the present invention is not limited to any of the examples and comparative examples.
[0068] <Example 1> <<First step>> 80 parts by volume of UENO LCP A5000 (melting point 280° C.) manufactured by Ueno Pharmaceutical Co., Ltd. as a liquid crystal polymer and 20 parts by volume of lithium chloride (powder, manufactured by Kanto Chemical Co., Ltd., average particle size 4.0 μm) as a pore-forming agent were kneaded by Labo Plastomill (trade name) (model: 100C100) manufactured by Toyo Seiki Co., Ltd. to prepare a composition. The temperature during kneading was 340° C., and the rotation speed of the screw in the kneading device was adjusted to 30 rpm (revolutions per minute: revolutions per minute).
[0069] Next, a nonporous film (nonporous film) having a thickness of 260 μm was produced from the kneaded product using a manual liquid vacuum press (model: 11FD) manufactured by Imoto Manufacturing Co., Ltd. The temperature during the pressing was 340° C. and the pressure was 4 MPa.
[0070] <<Second step>> The pore-forming agent was extracted from the membrane obtained in the first step using a "CO2 supercritical fluid experimental apparatus" manufactured by Shinko AirTech Co., Ltd., using supercritical carbon dioxide as a supercritical fluid. Methanol was used as the entrainer (the amount of the entrainer used was set to 10 wt % relative to the amount of carbon dioxide used in the treatment). The temperature of the supercritical carbon dioxide in the third step was 150° C., the pressure of the supercritical carbon dioxide was 30 MPa, and the impregnation time (extraction time) was 180 minutes.
[0071] <<Third step>> While removing the supercritical carbon dioxide in the pressure vessel, the pressure of the pressure vessel was reduced to return to atmospheric pressure, and the heating was stopped. Thus, a porous liquid crystal polymer film (porous film) having a thickness of 260 μm was obtained.
[0072] <Example 2> In Example 1, a porous liquid crystal polymer film (porous film) was obtained in the same manner as in Example 1 except that the pore-forming agent was changed to lithium chloride having an average particle size of 65 μm.
[0073] <Example 3> In Example 1, a porous liquid crystal polymer film (porous film) was obtained in the same manner as in Example 1 except that the mixing ratio of lithium chloride was changed to 60 parts by volume relative to 40 parts by volume of the liquid crystal polymer.
[0074] <Example 4> In Example 2, a porous liquid crystal polymer film (porous film) was obtained in the same manner as in Example 2 except that the mixing ratio of lithium chloride was changed to 60 parts by volume relative to 40 parts by volume of the liquid crystal polymer.
[0075] <Comparative Example 1> UENO LCP A5000 (melting point 280° C.) manufactured by Ueno Pharmaceutical Co., Ltd. was kneaded using Labo Plastomill (trade name) (model: 100C100) manufactured by Toyo Seiki Co., Ltd. The kneading temperature was 340° C., and the screw rotation speed in the kneading device was adjusted to 30 rpm (revolutions per minute).
[0076] Next, a nonporous film (nonporous film) having a thickness of 260 μm was produced from the kneaded product using a manual hydraulic vacuum press (model: 11FD) manufactured by Imoto Manufacturing Co., Ltd. The temperature during the pressing was 340° C. and the pressure was 4 MPa.
[0077] <Pore area ratio, pore size, average pore size> The area ratio and the average pore size were determined as follows. Platinum was evaporated on the surface of the liquid crystal polymer film to obtain an observation sample. The surface of the observation sample was observed by SEM (scanning electron microscope; SU8020, manufactured by Hitachi High-Technologies Corporation, accelerating voltage 2.0 kV) to obtain a SEM image. The obtained SEM image was analyzed. Image analysis was performed using Image-J, which is a public image processing software. Specifically, it was performed as follows. Import the SEM image into Image-J. Calculate the area ratio of the holes based on the number of pixels of the holes that are relatively dark in the SEM image and the number of pixels of other parts. For the hole size, the longest part of the hole is set as the hole size. The average hole size is calculated by dividing the sum of the hole sizes by the number of holes. When the SEM image was loaded into Image-J, black-and-white binarization was performed to distinguish the pores from other parts. The standard conditions of Image-J were used for the threshold value during the binarization process. The results are shown in Table 1.
[0078] <Porosity> The porosity was calculated using the following formula. The results are shown in Table 1. Porosity [%] = 100 × {(M i -M p ) / M i} ·M i : Specific gravity of liquid crystal polymer ·M p : Specific gravity of porous membrane
[0079] <Dielectric constant and dielectric loss tangent> The dielectric constant (Dk) and dielectric loss tangent (Df) of the liquid crystal polymer film at 10 GHz were measured by the SPDR method (split dielectric resonance method) according to ASTM D150 using a "10 GHz SPDR resonator" manufactured by QWED.
[0080] <Peel strength> As an evaluation of adhesion, the peel strength was measured. The preparation method and measurement method of the test sample are as follows. A copper foil with a thickness of 18 μm was bonded to an adhesive sheet A27F (manufactured by Arisawa Manufacturing Co., Ltd.; equivalent to a thermoplastic resin) and processed into a strip of 110 mm in length and 5 mm in width to obtain a BS / Cu strip. The bonding was performed using a calender roll with a roll speed of 0.5 m / min, a roll temperature of 80° C., and a roll pressure of 1 MPa. Five BS / Cu strips were bonded to a liquid crystal polymer film with the five BS / Cu strips spaced at a certain interval and the adhesive sheet surface in contact with the liquid crystal polymer film to obtain a test sample (150 mm in length × 50 mm in width). It should be noted that bonding was performed by heat and pressure treatment at 170°C, 120 seconds, 4 MPa, and then post-baking at 180°C for 1 hour. The test sample was placed on the surface of a pulley with a diameter of 15 cm installed in a tensile testing machine (TG series, manufactured by Minebea Co., Ltd.) and a 90-degree peel test was performed. Specifically, the liquid crystal polymer film in the test sample was fixed to the surface of the pulley using a double-sided tape. The BS / Cu strip of the test sample was fixed to the chuck of the tensile testing machine, and the chuck was pulled up at a speed of 50 mm / min in a direction of 90 degrees relative to the plane of the pulley to measure the peel strength between the liquid crystal polymer film and the adhesive sheet. The peel strength of each liquid crystal polymer film was measured five times, and the average value thereof was calculated and used as the peel strength.
[0081] [Table 1] Explanation of symbols
[0082] 1: Conductor layer 2: Thermoplastic resin layer 3: Liquid crystal polymer film.
Claims
1. A liquid crystal polymer film, wherein: The liquid crystal polymer film has pores on the surface, When the surface of the liquid crystal polymer film is observed, the area ratio of the pores to the surface is 0.50% or more.
2. The liquid crystal polymer film according to claim 1, wherein The liquid crystal polymer film is a porous film.
3. The liquid crystal polymer film according to claim 1, wherein The average size of the pores is 10 μm or less. 4 . A laminate comprising: the liquid crystal polymer film according to claim 1 ; a thermoplastic resin layer; and a conductor layer.
Citation Information
Patent Citations
Aromatic liquid crystal polyester solution composition
JP2004189867A
Method for manufacturing metal coated liquid crystal polyester substrate
JP2004307980A
Resin composition
JP2020147670A